2014
DOI: 10.1111/1365-2664.12274
|View full text |Cite
|
Sign up to set email alerts
|

Conservation management within strongholds in the face of disease‐mediated invasions: red and grey squirrels as a case study

Abstract: Summary1. There is increasing evidence that disease-mediated invasions are widespread across a range of vertebrate, invertebrate and plant systems. We therefore need a better understanding of the role of disease in managing conservation threats due to introduced and invasive species. 2. Here, we develop a general theoretical model framework to assess the impact of diseasemediated invasion on the viability of conserving native species through refuges taking into account explicit spatial and stochastic processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 40 publications
(57 reference statements)
0
26
0
Order By: Relevance
“…This is consistent with the results obtained through other models. For instance in [52], it was also found that, in the absence of control of the invading species, native populations are driven to extinction and that this occurs both in the absence of disease (through competition only; see also [25,43]) and more rapidly when the disease is included [28]. Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the results obtained through other models. For instance in [52], it was also found that, in the absence of control of the invading species, native populations are driven to extinction and that this occurs both in the absence of disease (through competition only; see also [25,43]) and more rapidly when the disease is included [28]. Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Again, [51,52] also found that grey squirrel control can protect red populations in strongholds, although in their specific case study, periodic outbreaks of the disease could not be prevented because of occasional recolonization of the stronghold by grey squirrels from neighboring areas. The work in [52] also highlighted that there is a threshold level of control (expressed as the proportion of grey squirrels to be removed), above which the invading population can be prevented from establishing and the native species can be protected. Another study [28] also investigated what level of population control of grey squirrels would be necessary to suppress the disease-induced decline in red squirrels.…”
Section: Equilibriummentioning
confidence: 99%
“…see [4,5]). The multiple introductions and subsequent translocations had devastating consequences for local Eurasian red squirrel populations in deciduous and mixed forest landscapes in Great Britain, Ireland and Italy leading to large-scale declines as a result of competition for resources and introduced pathogens [6][7][8]. With regard to pathogens, the replacement of native Eurasian red squirrels by the Eastern grey squirrels in the British Isles is highly accelerated by a squirrelpox virus (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have synthesized techniques from mathematical epidemiology with metapopulation models (Hess, 1996;McCallum and Dobson, 2002) or developed stochastic simulation models based on underlying epidemiological frameworks that represent the dynamics on an array of patches connected in a simplied manner (Hess, 1996;White et al, 2014). The most similar study to ours used an individual-based, stochastic disease model to represent the dynamics on a two-dimensional lattice of identical patches with nearest neighbour dispersal (Cross et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous theoretical studies which have examined infection dynamics have used classical Levins (Levins, 1969) metapopulation approaches (Hess, 1996;McCallum and Dobson, 2002), simulation methods with an idealised spatial set-up, such as patches connected in a linear or looped array (Hess, 1996;White et al, 2014), or a two-dimensional lattice of homogeneous patches (Cross et al, 2005). However, despite the heterogeneity of natural landscapes and habitats, the incorporation of detailed, realistic landscape structure has been less well explored (Ostfeld et al, 2005).…”
Section: Introductionmentioning
confidence: 99%